Algal Mediated Green Synthesis Of Silver Nanoparticles Using Turbinaria Ornata. - S, Rasveya; Francis , Marina M; Ramachandran , Sathish Kumar (Journal of Neonatal Surgery, 2022)
Background Information:Nanoparticles exhibit improved performance due to their large surface to volume ratio. T. Ornata is a brown alga, which is widely distributed in the tropical and subtropical seas were selected for the synthesis of silver nanoparticles. This brown alga is composed of many bioactive compounds. These secondary metabolites contain functional groups which can reduce the silver ions to silver and act as stabilizing agent for nanoparticles. Materials and methods:Brown seaweed Turbinaria Ornata was collected at the Gulf of Mannar region (latitude 78° 8’ East and longitude 9° 17’ North) along the eastern coast of Tamil Nadu, India. The collected seaweeds were cleaned thoroughly to avoid salts, sand, shells, debris with associated epifauna and epiphytes. Cleaning was done by tap water and rinsing with double distilled water. Furthermore, the seaweeds were allowed to dry in the shade for over a week. Then, the dried seaweeds were crushed or grounded and aqueous extract preparations Synthesis of silver nanoparticles and estimation of anti-oxidant and anti-cancer activity were performed. Results:The SEM results depicts that the obtained silver nanoparticles were cubical in shape. The UV-Vis spectra confirms the biosynthesis of silver nanoparticles at 438 nm. The presence of AgO nanoparticles is confirmed by the spectrum vibration at 815 cm-1. The EDX confirms the presence of silver nanoparticles. The significant anti-oxidant potential of AgO nanoparticles was evaluated by DPPH radical scavenging assay having concentration of 50 µg. The ascorbic acid was used as a standard. The cytotoxic activity on breast cancer cell lines shown decreasing the cell viability by increasing the concentration of silver nanoparticles. Conclusion:The synthesized AgNPs is found to have a potential anti-oxidant activity and has cytotoxic effect against breast cancer cell line. Further, it has to be analyzed for other biomedical applications so as to present it as an effective agent in future